Tinjauan Lampu Lalu Lintas Persimpangan Goa Ria, Makassar Menggunakan Metode PKJI 2014 - Ika Apriyani; Robert Mangontan; Alex Sandria Tato (Program Studi Teknik Sipil UKI Paulus-Makassar, 2023)
The population and count of vehicles in Makassar City as the capital city of South Sulawesi Province, continues to increase every year, so that traffic flow increases. For this reason, it must be supported with adequate service facilities, especially on routes that can cause congestion if not handled technically. One example of a signalized intersection where long queues often occur is the Goa Ria intersection in Biringkanaya District, Makassar City Using the 2014 PKJI Method. The research location at the intersection of Jalan Goa Ria, Biringkanaya District is a three-signalized intersection. At this intersection congestion, queues and delays often occur due to heavy traffic, especially during rush hour. Based on the problems above, the signalized intersection on Jalan Goa Ria, Biringkanaya District needs to be reviewed regarding traffic light settings using the PKJI 2014 method as an update from MKJI 1997. The results of the Traffic Light Review at Goa Ria Intersection, Biringkanaya District obtained traffic light settings on The Goa Ria intersection, Biringkanaya District is less effective because based on calculations using the 2014 Indonesia Road Capacity Guidelines it produces different traffic light cycle time values ​​and high queue length and delay values, especially on the north arm. Traffic volume at the Goa Ria intersection, Biringkanaya sub-district occurs during the afternoon peak hours with the volume on the North arm 1182 pcu/hour, East 152.8 pcu/hour, and South 955.8 pcu/hour.